Governance And Youth Empowerment Initiatives In Nigeria: To What Extent Has It Curbed Crime Rates? - Adegbami, Adeleke; Egugbo, Cletus Chuks (Journal of Governance and Administrative Reform, 2025)
Abstract The study investigates the need for youth empowerment, the barriers hindering youth empowerment programs, and the extent to which these programs have been effective in reducing crime and criminal activities in Nigeria. It draws upon secondary data, including textbooks, academic journals, government documents, newspapers, and online sources, which were analyzed using content analysis. The findings highlight that youth empowerment is essential for enabling young people to assume leadership roles, foster innovation and creativity, and contribute to the nation's economic growth and development. Regarding the barriers to youth empowerment programs, the study identifies several challenges: reluctance among youth to participate in empowerment initiatives, a lack of awareness about the benefits of these programs, inadequate or insufficient funding, a lack of transparency among those managing youth empowerment efforts, misappropriation of funds, distractions from social media, and a prevailing mentality among youth focused on quick financial gains. Furthermore, the study reveals that the current structure and implementation of youth empowerment programs in Nigeria are insufficient to address the needs of the large youth population. Despite various empowerment initiatives introduced by successive Nigerian administrations, the study concludes that persistent socio-economic crises evidenced by limited access to education and skills development, rising unemployment rates, and widespread poverty and hunger continue to plague the country. Without addressing these foundational issues, crime and criminal activities are likely to persist. In light of these findings, the study recommends the ongoing and deliberate development of the youth population's capacities as a critical step toward fostering a peaceful environment and achieving national development. Keywords: governance; youth empowerment; unemployment; poverty; hunger and crimes.   Abstrak  Penelitian ini menyelidiki kebutuhan pemberdayaan pemuda, hambatan-hambatan yang menghalangi program pemberdayaan pemuda, dan sejauh mana program-program tersebut efektif dalam mengurangi kejahatan dan aktivitas kriminal di Nigeria. Penelitian ini mengandalkan data sekunder, termasuk buku teks, jurnal akademik, dokumen resmi pemerintah, surat kabar, dan sumber-sumber daring, yang dianalisis menggunakan analisis konten. Temuan penelitian ini menunjukkan bahwa pemberdayaan pemuda sangat penting untuk memungkinkan generasi muda mengambil peran kepemimpinan, mendorong inovasi dan kreativitas, serta berkontribusi pada pertumbuhan dan perkembangan ekonomi negara. Terkait dengan hambatan-hambatan pada program pemberdayaan pemuda, penelitian ini mengidentifikasi beberapa tantangan: ketidakinginan pemuda untuk berpartisipasi dalam inisiatif pemberdayaan, kurangnya kesadaran tentang manfaat program-program tersebut, alokasi dana yang tidak memadai atau tidak mencukupi, kurangnya transparansi di antara mereka yang mengelola upaya pemberdayaan pemuda, penyalahgunaan dana, gangguan dari media sosial, dan mentalitas pemuda yang lebih fokus pada pencapaian keuntungan finansial secara cepat. Selain itu, penelitian ini mengungkapkan bahwa struktur dan pelaksanaan program pemberdayaan pemuda yang ada di Nigeria saat ini tidak cukup untuk memenuhi kebutuhan populasi pemuda yang besar. Meskipun berbagai inisiatif pemberdayaan telah diperkenalkan oleh pemerintahan-pemerintahan yang berganti di Nigeria, penelitian ini menyimpulkan bahwa krisis sosial-ekonomi yang terus berlanjut yang terlihat dalam terbatasnya akses terhadap pendidikan dan pengembangan keterampilan, meningkatnya tingkat pengangguran, serta kemiskinan dan kelaparan yang melanda terus menghantui negara. Tanpa mengatasi masalah-masalah mendasar ini, kejahatan dan aktivitas kriminal kemungkinan besar akan terus terjadi. Berdasarkan temuan-temuan tersebut, penelitian ini merekomendasikan pengembangan kapasitas populasi pemuda secara berkelanjutan dan terencana sebagai langkah krusial untuk menciptakan lingkungan yang damai dan mencapai pembangunan nasional. Kata kunci: tata kelola pemerintah; pemberdayaan pemuda; pengangguran; kemiskinan; kelaparan dan kejahatan.